STUDENTS INTEREST IN CONTINUING PROFESSIONAL EDUCATION NURSES IN HEALTH EDUCATION INSTITUTIONS IN BANYUMAS - Rahmaya Nova Handayani; Adiratna Sekarsiwi (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2015)
Introduction. Types of nursing education in Indonesia are vocational, academic and professional. Professional education is higher education after an undergraduate program that prepares students to have jobs with specific skill requirements. The purpose of this study was to identify factors that affect student interest in continuing professional education nurses based on perception, motivation and support system. Method. The study design was a descriptive analytic cross-sectional approach. Unstratified sampling using random sampling with a sample of 111 respondents in health education institutions in karisidenan Banyumas, there are Harapan Bangsa Purwokerto Institute of Health Science, Purwokerto Muhammadiyah University, Jenderal Sudirman University.Data was analysed by using multivariate logistic regression. Results. The results of the study showed that no correlation  perception, motivation, and support system of nurses Profession election interest in health education institutions in-karisidenan Banyumas (p=0,999; 0,956; 0,135).Discussion. The most dominant factor affecting the interest of the nurse profession was support system.Keywords: interest, perception, motivation, support system, professional nurses